BIAYA PEMASANGAN BARU DAN PERHITUNGAN REKENING LISTRIK GOLONGAN TARIF RUMAH TANGGA - Mukhlis, Baso (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2012)
The problem of the society when it will require new electrical connection to PLN especially household bill level is the ignorance on the procedure and costwhich have to be paid so that it asks helping to the brokers. This paper describes about how to calculate cost of new connection installing which must be paid to PLN based on Kepmen ESDM No : 07 Tahun 2010, cost of electrical installation based on the amount of the power required, and how to calculate cost of usage based on new base rate2010. Key words: electric base rate, new connection cost, installer cost